Evidence for verbal memory enhancement with electrical brain stimulation in the lateral temporal cortex - Kucewicz, Michal T; Berry, Brent M; Miller, Laura R; Khadjevand, Fatemeh; Ezzyat, Youssef; Stein, Joel M; Kremen, Vaclav; Brinkmann, Benjamin H; Wanda, Paul; Sperling, Michael R; Gorniak, Richard; Davis, Kathryn A; et al. (Brain, 2018)
Direct electrical stimulation of the human brain can elicit sensory and motor perceptions as well as recall of memories. Stimulating higher order association areas of the lateral temporal cortex in particular was reported to activate visual and auditory memory representations of past experiences (Penfield and Perot, 1963). We hypothesized that this effect could be used to modulate memory processing. Recent attempts at memory enhancement in the human brain have been focused on the hippocampus and other mesial temporal lobe structures, with a few reports of memory improvement in small studies of individual brain regions. Here, we investigated the effect of stimulation in four brain regions known to support declarative memory: hippocampus, parahippocampal neocortex, prefrontal cortex and temporal cortex. Intracranial electrode recordings with stimulation were used to assess verbal memory performance in a group of 22 patients (nine males). We show enhanced performance with electrical stimulation in the lateral temporal cortex (paired t-test, P = 0.0067), but not in the other brain regions tested. This selective enhancement was observed both on the group level, and for two of the four individual subjects stimulated in the temporal cortex. This study shows that electrical stimulation in specific brain areas can enhance verbal memory performance in humans.awx373media15704855796001.
Keywords: epilepsie; Female; lidé středního věku; mapování mozku; hluboká mozková stimulace; Temporal Lobe; mužské pohlaví; mladý dospělý; verbální učení; spánkový lalok; Memory Disorders; Humans; dospělí; časové faktory; Deep Brain Stimulation; lidé; Middle Aged; Time Factors; Brain Mapping; ženské pohlaví; poruchy paměti; Young Adult; Verbal Learning; Adult; Epilepsy; Male